IMPLICATIONS OF THE UKRAINE RUSSIAN INVASION ON HUMAN RIGHT AND THE INTERNATIONAL ECONOMY: IMPLIKASI INVASI RUSIA UKRAINA TERHADAP HAMA DAN PEREKONOMIAN INTERNASIONAL - Kristo Saputra Criss; Randita Putri Nugraini; Chairunisa Alya Rahmawaty (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2023)
The impact given to the war that occurs between one country and another, will certainly have implications and greatly affect other countries that are not involved in the war, one of which a large effect on the economic sector. so that the impact of the war occurs so that the economy will take root again, new problems and spread to various countries. Concrete examples of contemporary issues that occurred, such as the invasion that occurred between Russia and Ukraine, which had a widespread impact, especially in the Southeast Asian Region. The approach or methodology used in this study is a literature research, based on the problems or issues raised regarding how and what impact the post-invasion had on the world economy and how solutions or policies could be taken in overcoming the consequences after the invasion ended, especially in the economic field has even taken the human rights of civilians which of course has a big impact so that it will be more analytical in nature from the various problem concepts raised and the relationship between the variables in this research to be made with factual data and technical analysis based on the best possible knowledge. The purpose of writing this article is to serve as a guideline and reference for further researchers regarding the impact of a war and its solutions after the war ends. Until the author also strives for no shortcomings, such as the correctness of the data taken, analysis of the issues raised, as well as the writing and structure of this article.